Study of conjugate heat transfer from the impingement of an inclined free slot jet onto the moving hot surface. (February 2020) - Pawar, Shashikant; Patel, Devendra Kumar
Abstract: A dimensionless numerical investigation of turbulent flow and heat transfer characteristics due to the impingement of a free inclined slot jet onto the moving hot surface has been performed using the k  −  ω turbulence model. The parameters considered for the investigation are: the Reynolds number, impingement angle and plate velocity. The influence of parameters on the properties such as the pressure and velocity profiles, skin-friction coefficients, Nusselt number, interface temperature, and the location of stagnation has been presented. The displacement of stagnation point depends primarily on ϕ, whereas the effect of plate velocity is less significant. These relocations are found in between X  = − 2 to 0. The effect of plate velocity on average skin-friction coefficient is continuously decreasing with increase in jet angle. A continuous increase in average Nu has been found with increase in Re for all values of ϕ and U p considered in the present study. It is revealed that the change in plate velocity has more influence on the average Nu for lower angles of impingement. Further reduction in the impingement angle shows an adverse effect on the average Nu . Correlations have been developed for Nusselt number at different zones based on the parameters considered for the study.